Geodata - Tobia Lakes (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Empirical data can be characterized by a precise location in space and time. An estimated 80% of all data holds such a spatio-temporal reference and is termed geodata. This paper starts with the question: What is the additional benefit for socio-economic sciences using geodata and the spatial dimension respectively? In the following a multidimensional approach is chosen to outline the Status Quo of geodata and spatial techniques in Germany. It is particularly the continuously growing amount and the variety of available geodata which is stated. Data security is an issue of high importance when using geodata. Furthermore, the present developments in price and user concepts, accessibility, technical standards and institutionalisation are addressed. A number of challenges concerning the field of geodata are identified including the open access to geodata, data security issues and standardization. The main challenge however seems to be the exchange between the rather segregated fields of geoinformation and the information infrastructure. Furthermore, the census 2011 is identified as a major challenge for the acquisition and management of geodata. Geodata and spatial techniques are a rapidly developing field due to technology developments of data and methods as well as due to recently growing public interest. Their additional be efit for socioeconomic research should be exploited in the future.
Keywords: 330; geodata; geoinformation; Web-GIS; geodata-infrastructure; spatial techniques